Science examination results in Barbados, Jamaica and Trinidad and Tobago - Whiteley, Peter N. (My University, 1992)
This paper presents science examination results in Barbados, Jamaica and Trinidad and Tobago at both the secondary and tertiary levels, within the context of the contribution of science education to the development of these three territories. Trends in the data are identified, and the comparisons made among the countries. Some of the factors that may be affecting the results are briefly discussed.
Biennial Cross-Campus Conference on Education, 2nd, St. Augustine, Trinidad, 22-24 April, 1992